Answer:
The second option is correct
Step-by-step explanation:
Recall,
![\sqrt[a]{b}\text{ = b}^{(1)/(a)}](https://img.qammunity.org/2023/formulas/mathematics/college/keope0xbx96likrqc2mgub2u2l37x0zvrq.png)
Thus, the given expression can be written as
5^(1/3) a^(1/3)b^(2/3) * 5^(2/3)a^(1/3)b^(1/3)
We would apply the rule of exponents which is expressed as
a^b * a^c = a^(b + c)
The expression becomes
5^(1/3) * 5^(2/3) * a^(1/3) * a^1/3 * b^(2/3) * b^(1/3)
= 5^(1/3 + 3/3) * a^(1/3 + 1/3) * b^(2/3 + 1/3)
= 5^(1) * a^(2/3) * b^(1)
= 5 * a^(2/3) * b^(1)
It becomes
![5b\sqrt[3]{a^2}](https://img.qammunity.org/2023/formulas/mathematics/college/gtm7d5ruahigbuxzphc1g4bhlo429p3ydh.png)
The second option is correct